Effect of Technology Parameters to the Shrinkage of Mango Slices during Convection Drying Process - Nguyen, Duc Trung; Pham, Thanh Huong (Old Journal, 2019)
Computer vision application to improve the effectiveness of quality evaluation and image sensory is an interested trend of researching in food processing. The range of technology parameters: velocity, temperature of drying air and material thickness which can ensure the acceptable quality and color of the dried mango slices is applied to estimate the effect of technology parameters to the shrinkage and deformation during convective drying process. This study utilizes the program developed in Matlab to determine the geometry parameters of 2D – object (the area, the dimension of long and short axis of fitted ellipse) in order to determine the shape variation from the images of mango slices and original sample with defined dimension and form.